2009
DOI: 10.1097/cad.0b013e32832ae55f
|View full text |Cite
|
Sign up to set email alerts
|

The marine alkaloid naamidine A promotes caspase-dependent apoptosis in tumor cells

Abstract: Apoptosis is important for normal development and removal of damaged cells. Evasion of apoptosis by cancer cells is one of the key characteristics of many tumor types. Thus, discovering agents that promote apoptosis in tumor cells could have great therapeutic value. Marine natural products have demonstrated great potential as anticancer agents, and the proapoptotic activity of some of these products is emerging as a potentially useful property for cancer treatments. Using a tumor xenograft assay in rodents, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 40 publications
0
33
0
Order By: Relevance
“…Therefore, using fluorescence-activated cell sorter (FACS) analysis [58,59], we measured neo’s effect on the cell cycle and apoptosis using SW48 cells treated with 0.60 μM neo for 48 h (Figure 3). Propidium iodide staining followed by FACS indicated that the percentage of cells in the G1 phase of the cell cycle were the same for both neo treated and control cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, using fluorescence-activated cell sorter (FACS) analysis [58,59], we measured neo’s effect on the cell cycle and apoptosis using SW48 cells treated with 0.60 μM neo for 48 h (Figure 3). Propidium iodide staining followed by FACS indicated that the percentage of cells in the G1 phase of the cell cycle were the same for both neo treated and control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Cell cycle and apoptosis experiments were conducted as previously reported with slight modification [59]. Briefly, SW48 cells (2 × 10 5 per well) were seeded into six-well plates and incubated for 24 h. Cells were treated with neo (0.6 μM) for 48 h, washed with PBS, and trypsinized with 0.5 mL of 0.25% trypsin.…”
Section: Methodsmentioning
confidence: 99%
“…The results presented in Figure 6 indicate that Compounds 4c and 5c promoted apoptosis in RKO-AS-45-1 and HeLa cells, reducing the number of viable cells. The apoptotic behavior of isolated or synthetic alkaloids is associated with mitochondrial membrane depolarization [38], phosphatidylserine externalization [39] and alteration of the patterns of cytoskeleton polymerization [40]. …”
Section: Resultsmentioning
confidence: 99%
“…To date, only the biological activity of naamidine A ( 3 ) has been extensively investigated by the Ireland lab which has demonstrated that it promotes caspase-dependent apoptosis in cultured tumor cells. 8 An Australian team has reported a modest exploration of the SAR of the naamine/naamidine A framework. 9 More recently, the Looper lab 10 and our group 11 have begun to evaluate the biological activity of synthetic versions of various other family members, specifically the naphthimidazole group.…”
Section: Introductionmentioning
confidence: 99%